2018
DOI: 10.1177/1460458218779114
|View full text |Cite
|
Sign up to set email alerts
|

Test results management and distributed cognition in electronic health record–enabled primary care

Abstract: Managing abnormal test results in primary care involves coordination across various settings. This study identifies how primary care teams manage test results in a large, computerized healthcare system in order to inform health information technology requirements for test results management and other distributed healthcare services. At five US Veterans Health Administration facilities, we interviewed 37 primary care team members, including 16 primary care providers, 12 registered nurses, and 9 licensed practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Characteristics of included studies chronologically ordered by publication date are outlined in Table 1. Studies comprised one randomised controlled trial (RCT), [34] 11 cohort, [16,18,19,21,22,24,25,[35][36][37][38] two cross-sectional, [23,27], two qualitative studies, [39,40] and two mixed method studies (cross-sectional and qualitative, [17] and cohort and qualitative) [26]. All studies were US-based, except one cohort study from the Netherlands [26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of included studies chronologically ordered by publication date are outlined in Table 1. Studies comprised one randomised controlled trial (RCT), [34] 11 cohort, [16,18,19,21,22,24,25,[35][36][37][38] two cross-sectional, [23,27], two qualitative studies, [39,40] and two mixed method studies (cross-sectional and qualitative, [17] and cohort and qualitative) [26]. All studies were US-based, except one cohort study from the Netherlands [26].…”
Section: Resultsmentioning
confidence: 99%
“…Failure to attend scheduled/recommended followup, [18,21,23,25,26,41] or any follow-up within a specified time, [19,22,27,[38][39][40] Failure to undergo complete follow-up to diagnostic resolution, [16,17,34,35] Failure of PCP to inform patient of abnormal mammogram result, [36] and PCP failed to acknowledge follow-up letter, was not aware of result or had no follow-up plan [37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the availability of an electronic test results management application, clinicians in the current study reported using a combination of both manual and electronic tracking strategies to ensure test results requiring follow-up were actioned (themes 1 and 5). This need to support “memory of pending tasks” 36 for managing test results and using paper-based strategies in HIT-enabled settings such as sticky notes, 17 , 35 lists, and logs, has been previously reported in the literature 17 , 18 , 35 , 36 and characterized as “workarounds.” 35 The paper and electronic tracking strategies we identified meet the definition of workarounds stated in Debono et al as “observed or described behaviors that may differ from organizationally prescribed or intended procedures.” 45 The context surrounding our participants’ adoption of workarounds are indicative of clinicians actively employing strategies to support the cognitive demands of tracking test results through to follow-up and completion. Thus, they also fall under the definition of resilience stated in Smith et al as “positive adaptability within systems that allows good outcomes in the presence of both favourable and adverse conditions.” 46 Although resilience strategies can maximize positive outcomes, they also risk obscuring underlying barriers or threats to safety.…”
Section: Discussionmentioning
confidence: 96%
“… 34 Another approach identified in a study of electronic management of abnormal cancer-related test results in a primary care setting, included a process in which the diagnostic service provider coded the importance of test results to allow primary care providers to prioritize their alerts. 36 …”
Section: Discussionmentioning
confidence: 99%